IMPLEMENTASI PRINSIP ISLAMIC CORPORATE GOVERNANCE DALAM PEDOMAN AMAL USAHA KESEHATAN - Berkah, Dian (Ahkam: Jurnal Hukum Islam, 2014)
Moslem scientists. Many analyze the corporate governancewithin the perspective of Moslem by which it comes up with aterm of Islamic Corporate governance. The next development ofcorporate governance is the emergence of good governance inclinic or hospital which is called as clinical governance. So far,there has not been any study dealing with how good governanceis implemented in a Islamic clinic. This study, therefore, is aneffort to scrutiny the implementation of the principles in IslamicCorporate governance at Pedoman Amal Usaha KesehatanMuhammadiyah.Kata kunci: Corporate governance, Islamic Perspective,Pedoman Amal Usaha Kesehatan